2021
DOI: 10.1039/d0sc05655c
|View full text |Cite
|
Sign up to set email alerts
|

Phenazines as model low-midpoint potential electron shuttles for photosynthetic bioelectrochemical systems

Abstract: Phenazines were explored as novel low-midpoint potential molecules for wiring cyanobacteria to electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 61 publications
2
67
0
Order By: Relevance
“…As an example, 2,6‐DCBQ is a quinone that prevents the cell growth at relatively low concentration. A similar effect was recently observed in the case of cyanobacteria [6b] . The results are in agreement with a redox potential‐activity relationship.…”
Section: Resultssupporting
confidence: 91%
“…As an example, 2,6‐DCBQ is a quinone that prevents the cell growth at relatively low concentration. A similar effect was recently observed in the case of cyanobacteria [6b] . The results are in agreement with a redox potential‐activity relationship.…”
Section: Resultssupporting
confidence: 91%
“…In 2021, Zhang et al reported the first use of phenazines as diffusible redox mediators specifically in conjunction with cyanobacteria ( Synechocystis sp. PCC 6803) in biophotovoltaics [ 100 ]. Redox potentials of phenazines generally range high enough to facilitate electron transfer from the cyanobacteria and low enough to cause marginal energy losses in overpotential.…”
Section: Exogenous E-met Via Diffusible Redox Mediatorsmentioning
confidence: 99%
“…Several studies have examined the impact of both naturally occurring as well as artificially synthesized phenazine derivatives on bacterial interaction and metabolism ( Askitosari et al., 2019 ; Pierson and Pierson 2010 ; Simoska et al., 2021 ; Venkataraman et al., 2011 ). Additionally, phenazine-based redox mediators have been exogenously added to improve the overall performance of microbial electrochemical systems ( Clifford et al., 2021 ; Simoska et al., 2021 ). For example, research has demonstrated that exogenously added phenazines improve electron transfer rates in microbial fuel cells ( Rabaey et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, phenazines have been used as a mediator system in microbial bioelectrochemical systems with other non-pathogen microorganisms, such as obligate aerobic Pseudomonas putida ( Askitosari et al., 2019 ; Schmitz et al., 2015 ), certain E. coli strains ( Feng et al., 2018 ), and cyanobacterium Synechocystis sp. ( Clifford et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%